CRITERIA OF FORMATION OF PROFESSIONAL PEDAGOGICAL COMMUNICATIVE COMPETENCE OF FUTURE TEACHERS - Kohut, Iryna V. (Educological discourse, 2015)
The criteria for characterization of the process of formation of professional pedagogical communicative competence of future teachers are looked throught in the article. It is given criteria, their indicators and levels (high, medium, low). It is characterized the methodology of determining the level of formation of professional pedagogical communicative competence of future teachers.